2021
DOI: 10.1111/dom.14362
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term (52‐week) efficacy and safety of dapagliflozin as an adjunct to insulin therapy in Japanese patients with type 1 diabetes: Subgroup analysis of the DEPICT‐2 study

Abstract: Aim: To examine the long-term efficacy and safety of dapagliflozin, a sodium-glucose co-transporter-2 (SGLT2) inhibitor used to treat type 1 diabetes, in the Japanese subpopulation of the DEPICT-2 study.Materials and Methods: Patients with type 1 diabetes were randomized to dapagliflozin 5 mg (n = 55), dapagliflozin 10 mg (n = 41) or placebo (n = 58) plus insulin for a 24-week, double-blind period followed by a 28-week, single-blind extension phase.Results: From baseline to 24 weeks, dapagliflozin reduced HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Moreover, Melin et al (2022 ) found that dapagliflozin pharmacokinetics was similar in adults with T1DM and T2DM. In addition, it was interesting to note that more and more research results suggested that dapagliflozin was a promising adjunct treatment to insulin which improves glycemic control in patients with inadequately controlled T1DM ( Dandona et al, 2017 ; Mathieu et al, 2018 ; Parkinson et al, 2019 ; Araki et al, 2020 ; Araki et al, 2021 ; Biester et al, 2021 ). Wang et al (2022 ) explored the quantitative relationship between dapagliflozin and loss of weight in T1DM patients and found that to achieve the plateau period in the loss of weight, 5 mg/day dapagliflozin was required for at least 41.6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Melin et al (2022 ) found that dapagliflozin pharmacokinetics was similar in adults with T1DM and T2DM. In addition, it was interesting to note that more and more research results suggested that dapagliflozin was a promising adjunct treatment to insulin which improves glycemic control in patients with inadequately controlled T1DM ( Dandona et al, 2017 ; Mathieu et al, 2018 ; Parkinson et al, 2019 ; Araki et al, 2020 ; Araki et al, 2021 ; Biester et al, 2021 ). Wang et al (2022 ) explored the quantitative relationship between dapagliflozin and loss of weight in T1DM patients and found that to achieve the plateau period in the loss of weight, 5 mg/day dapagliflozin was required for at least 41.6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of dapagliflozin is to promote glycemic disposal in an insulin-independent way, thereby decreasing postprandial glycemia and glycemic excursions accompanied by an inferior insulin demand without increasing the risk of hypoglycemia ( Li et al, 2022 ). It is interesting to note that research results suggest that dapagliflozin is a promising adjunct treatment to insulin which improves glycemic control in patients with inadequately controlled T1DM ( Dandona et al, 2017 ; Mathieu et al, 2018 ; Parkinson et al, 2019 ; Araki et al, 2020 ; Araki et al, 2021 ; Biester et al, 2021 ); meanwhile, it significantly decreases the glycated hemoglobin (HbA1c) ( Li et al, 2022 ). HbA1c identifies average plasma glucose concentration, and for people with diabetes this is important as the higher the HbA1c, the greater the risk of developing diabetes-related complications ( Rydberg et al, 2022 ; Wikstrom et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…SGLT-2 inhibitors were a group of antidiabetic drugs, which had the ability to reduce the blood sugar via inhibiting SGLT-2 [ 24 ]. Furthermore, except for lowering blood sugar [ 25 30 ], SGLT-2 inhibitors also had abilities to lose weight [ 24 , 31 , 32 ], reduce cardiovascular outcomes and mortality risk [ 33 ], and play renal protective effect [ 15 ]. It was also reported that SGLT-2 inhibitors could observably lower the response of inflammatory and smaller infarct size compared with other oral antidiabetic drugs, not dependent on blood sugar control [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of T2DM treatment and care were very challenging because they involved the prevention of organ damage and complications [23], including chronic damage and dysfunction of various tissues, especially kidneys [4], blood vessels [5], nerves [6], and heart [7], among SGLT-2 inhibitors were a group of antidiabetic drugs, which had the ability to reduce the blood sugar via inhibiting SGLT-2 [24]. Furthermore, except for lowering blood sugar [25][26][27][28][29][30], SGLT-2 inhibitors also had abilities to lose weight [24,31,32], reduce cardiovascular outcomes and mortality risk [33], and play renal protective effect [15]. It was also reported that SGLT-2 inhibitors could observably lower the response of inflammatory and smaller infarct size compared with other oral antidiabetic drugs, not dependent on blood sugar control [34].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 13 trials covering results for 10,701 patients (5,669 women and 5,032 men) were involved in the analysis. The mean study duration was 41.54 ± 14.47 weeks (Supplementary Materials Table S1) (15,16,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Identified Publicationsmentioning
confidence: 99%